LITERATION WORKSHOP FOR PARENTS ABOUT THE HAZARD OF COVID-19 AND ITS EFFECTS ON THE MIND AND MENTAL PATTERN OF CHILDREN - Emil Septia; Aruna Laila; Wahyudi Rahmat (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2020)
Literacy is very important for parents during a pandemic like today. Parental policy in observing information is highly demanded to understand whether the news obtained actually happened or was just a lie. Knowledge to understand related information with covid-19 really helps parents to organize the mindset and mental patterns of children. Because the information that is growing related to Covid-19 is very damaging to the mind and mental health of children. This happens because the child indirectly hears the danger of Covid-19 from people who are there surroundings, as well as from electronic media so. As a result, the child will feel afraid, because it is not accompanied by a clear explanation to the child about what he hears. For this reason, parental knowledge literacy plays a very important role in the development of children's thinking and mental patterns. The results of this workshop can be seen that the importance of linguistic literacy that needs to be known and controlled by the community, especially parents, to avoid the dangers of the Covid-19 outbreak and can affect the formation of children's thinking and mental patterns.